Growth in Commuting Distances in French Metropolitan Areas - The case of Paris - Anne Aguilera (European Regional Science Association (ERSA), 2005)
The continuous increase in the average commuting distance that characterizes European and North-American metropolitan areas is mainly the consequence of two developments. On one hand, the number of people living in a metropolitan area but working in another is on the increase. On the other hand, people living and working within the same metropolitan area are increasingly living further and further from their place of work: the 1999 and 1990 French censuses emphasize that the average (intra-metropolitan) distance from home to work has grown by 16% over the last decade. In particular, the municipality of residence is becoming increasingly different from the municipality of work. Such changes in commuting patterns, especially in the development of inter-municipality commutes, are promoting increased regular car use. These findings explain the growing interest in the relationship between urban form and commuting patterns. Given that most metropolitan areas are becoming polycentric, a body of research investigates whether polycentric distribution of people and jobs would be likely to re-organize mobility patterns in a more sustainable way. A key question is whether the development of employment subcenters would be likely to favor the co-location of workers and jobs in the suburbs and then to counteract increasing home-to-work distances. Most polycentric urban models are indeed based on the premise that people tend to locate within or close to their employment subcenter. But empirical studies tend to be more contradictory. In France, although many recent studies have underlined the development of subcenters inside most metropolitan areas and especially the biggest, links between polycentrism and commuting patterns have not been widely discussed. Urban sprawl in general is felt to be responsible for the growth of the average commuting distance insofar as the further the people live from the central city, the longer they spend commuting. But the specific impact of polycentrism and in particular the co-location hypothesis, i.e. the place of residence of those working in a subcenter, have not been questioned. In this paper two specific questions are raised. Are the people who live in a subcenter also employed in this subcenter? And do the (other) people working in a subcenter live close to this subcenter? If we compare the answers to these two questions in 1990 and in 1999, we can assess whether the situation is better or worse (in terms of proximity to place of work) in 1999 than ten years previously. The empirical work focuses on Paris which is the largest French metropolitan areas. Our findings emphasize that, although there are more jobs than working residents in all the subcenters, most people living in a subcenter work outside their subcenter of residence. This situation was also more marked by 1999 than it previously was in 1990. As a result, average commuting distances have increased for people living in a subcenter. In addition to this, the majority of jobs located in subcenters are filled by non-residents who generally live quite far from their employment subcenter, and indeed further in 1999 than they did in 1990. In conclusion we suggest some guidelines for future research.
Keywords: 330